Amidas aromáticas como modelos supramoleculares: de polimorfos a cocristais - Pagliari, Anderson Berti (2022)
This work explores using aromatic amides as models for understanding the characteristics of packing in the solid-state arising from structural changes. These models were adopted for their molecular simplicity, allowing the restriction of packing effects and behaviors, with great relevance in the pharmaceutical industry. Results of interactions dispute, flexibility, topology, and summation of interactions modulate and compete with each other at the supramolecular level. This work aims to study the causes and consequences of these changes. Events in the solid-state with self-organized systems (self-associated or heteroassociated) are evaluated by studying the crystallization mechanisms of cocrystals, solvates, and polymorphs. Thus, supramolecular clustering was used as a demarcation in conjunction with theoretical and experimental tools to support the data presented. Crystallization mechanisms were also proposed. A scope of molecules containing only amides and phenyl/perfluorfenyl rings reveals a complementarity between NH···O=C and interactions ···, as could be observed in the formation of a new cocrystal. Aromatic rings similar in their atoms tend to make interactions ··· within the formed ribbons and CH(F)··· interactions between them; however, in the complementary presence of phenyl/perfluorfenyl, only ··· it was observed. This complementarity between aromatic rings also gave rise to a strong hydrogen bond of −11,21 kcal mol−1, more energetic than those found in similar cocrystals. Structural modifications in isoxazole-containing benzamides showed that each change led to changes in crystal packing. Amide and isoxazole tend to form NH···Nisox interactions via closed dimers. This case is not observed when exchanging the heterocycle (furan). Bulky groups such as tert-butyl and the absence of NH at the amide site also favor CH··· interactions and stacking, increasing the role of topology in these systems. Aromatic bisamides containing isoxazole have led to polymorphs and solvates. A key point for forming the polymorphs was the energetic similarity between the amide-amide and amide-isoxazole nuclei, which alternate with each other with a change in packing. The presence of DMSO in the medium provided sufficient energy and topology so that there was no competition with self-association, leading to the formation of a solvate. Thus, polymorphs are attributed to energy balance and conformational flexibility. This knowledge can be used to design new solids with desirable properties and characteristics.